Spatial distribution of trace elements in surface sediments of Tien Yen Bay, northeast Vietnam - Quy, Tran Dang; Tue, Nguyen Tai; Nhuan, Mai Trong (Vietnam Journal of Earth Sciences, 2012)
The Tien Yen Bay in Quang Ninh province (northeast Vietnam) is abundant in natural resources, such as mangrove ecosystems, wetlands, and other biological resources. These ecosystems are highly sensitive to environmental pollution (i.e., trace element concentration). Yet, there still remains a major deficiency of information on trace element concentrations from the region. The purpose of this study was to examine the spatial distribution of 13 trace elements (Ni, Co, V, Cd, Cu, Mn, Mo, Cr, Pb, Zn, As, Hg, Sb) in surface sediments of Tien Yen Bay, in order to understand the mechanisms of trace element concentrations and to assess sediment quality. The results showed that the surface sediments were composed of sandy mud, muddy sand, and sand. The trace elements were highly concentrated in sediments close to river mouths and were decreased toward offshore and southeastern part of the bay. The trace elements positively correlated with each other. The trace element concentrations were controlled by the TOC content and the fine sediment grain size (<0,063mm). According to the Canadian ISQGs, Geo-accumulation index, and Pollution load index, the surface sediments were contaminated by trace elements (As, Hg, Sb, Cu, Pb, Zn, Cd, Cr, Mo).